VIRTUAL SOCIO-RELIGIOUS EMPOWERMENT: ADDRESSING SOCIAL FIQH CHALLENGES AMONG MUSLIM YOUTH IN EUROPE AND THE MEDITERRANEAN - Rizaldy Anggriawan; Agustiyara; Rofi Aulia Rahman; Muhammad Khoiru Ribath (Prime Identity Publisher, 2026)
Living as a Muslim minority in Europe presents complex socio-religious challenges for the Indonesian diaspora, particularly youth who must constantly navigate secular legal frameworks and diverse cultural norms. To address these daily practical dilemmas, the Special Branch of Muhammadiyah Youth Association in Europe and Mediterranean, in collaboration with PCIM Hungary, implemented a cross-border digital community engagement initiative. This program featured an interactive webinar focused on